Characterization of β-Globin Gene Cluster Deletions Using Multiplex-Gap Polymerase Chain Reaction (PCR) and Multiplex Ligation-Dependent Probe Amplification (MLPA) (Bangladesh Journal of Medical Science, 2021)
Background : Deletions in the β-globin gene cluster are usually rare, problematic to detect, and subsequently possess a challenge in many diagnostic laboratories. They are normally related to the heterozygous of the delta beta (δβ) thalassemia, hereditary persistence of fetalhemoglobin (HPFH) and some of the hemoglobin variants. These disorders are typically presented by elevated levels of hemoglobin F (Hb F), but with low to normal hemoglobin A2 (Hb A2). However, despite their existence, there is still a limited number of studies focusing on this area, hence no definitive diagnosis could be conclusively established. Therefore, this pilot study was carried out to fill this knowledge gap.Methods: In this study, screening of the selected deletional mutations in the β-globin gene cluster among patients with Hb F (>1%) and Hb A2 (